PENERAPAN PEMBELAJARAN KOOPERATIF MODEL THINK PAIRS SHARE (TPS) TERHADAP HASIL BELAJAR PADA MATA PELAJARAN SISTEM KOMPUTER SISWA KELAS XI JURUSAN RPL SMK NEGERI 2 PADANG - Silvia Yulanda (Universitas PGRI Sumatera Barat, 2021)
The purpose of the research is to explain the hrgher percentage of increasing students’ score in using Think Pairs Share (TPS) strategy in learning computer system at SMK N 2 Padang in the academic year 2017/2018. This in an experiment research, that hold on March 27th until April 11th 2018 at SMK N 2 Padang. The population of the research are XI students of RPL majon’ty at SMK N 2 Padang. The XI students of majon’ty RPL1 and RPL 2 as control classes that choosen by the using Simple Random Sampling. Bosed on the experiment, the average students’ score in the experiment class is 84,33 than the control classes 77,93. From the hypothesis (H0) was rejected an hypothesis (H1) received the result of the research is Think Pairs Share (TPS) strategy give increasing and improvement towards students’ score in learning computer system at SMK N 2 Padang.